Pengenalan Teknologi Canva Upaya Meningkatkan Keterampilan Desain Grafis Pada SMA/Sederajat Kabupaten Banyumas - Ardianto, Rian; Al-Hakim, Rosyid Ridlo; Jayusman, Hadi; Dewa, Bala Putra; Wibisono, Sony Kartika (Jurnal Arba - Multidisiplin Pengabdian Masyarakat, 2024)
The delivery of engaging, creative, and informative information is crucial to ensuring educational material is well understood by readers, particularly students in schools. The objective of this community service initiative is to foster creativity and encourage innovation in graphic design among equivalent high school students in Banyumas Regency. Training sessions on the use of the Canva application were conducted for high school students, utilizing practical demonstrations in the laboratory facilities of Universitas Harapan Bangsa, as part of the themed campus branding event known as CSC Fusion Camp organized by the Computer Science Club's Student Activity Unit. The training curriculum encompassed account creation, template utilization, and element arrangement for slide production as instructional support. Results from these activities indicated that participants successfully applied what they learned directly from the training modules. An evaluation was conducted through questionnaires assessing the usability of Canva, clarity of the materials, and perceived benefits by the participants. It is anticipated that this training will enhance students' insights and knowledge in delivering engaging and comprehensible learning materials tailored to their needs. Recommendations for future implementations include the necessity for advanced training sessions to enable students to maximize their application of the knowledge gained from this training.